An Annotated Chromosome-Level Reference Genome of the Red-Eared Slider Turtle (Trachemys scripta elegans) - Brian Simison, Warren (Genome Biol Evol, 2020)
Among vertebrates, turtles have many unique characteristics providing biologists with opportunities to study novel evolutionary innovations and processes. We present here a high-quality, partially phased, and chromosome-level Red-Eared Slider (Trachemys scripta elegans, TSE) genome as a reference for future research on turtle and tetrapod evolution. This TSE assembly is 2.269 Gb in length, has one of the highest scaffold N50 and N90 values of any published turtle genome to date (N50 = 129.68 Mb and N90 = 19 Mb), and has a total of 28,415 annotated genes. We introduce synteny analyses using BUSCO single-copy orthologs, which reveal two chromosome fusion events accounting for differences in chromosome counts between emydids and other cryptodire turtles and reveal many fission/fusion events for birds, crocodiles, and snakes relative to TSE. This annotated chromosome-level genome will provide an important reference genome for future studies on turtle, vertebrate, and chromosome evolution.